Improving voluntary public good provision by a non-governmental, endogenous matching mechanism: Experimental evidence - Christiane Reif; Dirk Rübbelke; Andreas Löschel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Social norms can help to foster cooperation and to overcome the free-rider problem in private provision of public goods. This paper focuses on the enforcement of social norms by a self-introduced punishment and reward scheme. We analyse if subjects achieve to implement a norm-enforcement mechanism at their own expense by applying the theory of non-governmental norm-enforcement by Buchholz et al. (2014) in a laboratory experiment. Based on their theory without central authority and endogenously determined enforcement mechanism, we implement a two-stage public good game: At the first stage subjects determine the strength of penalty/reward on their own and in the second stage they decide on their contributions to the public good. We find that the mechanism by Buchholz et al. (2014) leads to a higher public good contribution than without the use of any mechanism. Only in a few cases groups end up with a zero enforcement mechanism. This result indicates that subjects are apparently willing to contribute funds for implementing an enforcement mechanism. Moreover, higher enforcement parameters lead to higher public good contributions in the second stage, although too high enforcement parameters lead to unreachable theoretical optima.
urn:nbn:de:bsz:180-madoc-372037
Keywords: H41; C92; 330; laboratory experiment; public good; matching mechanism; social norms; norm enforcement